Implementasi Kebijakan Pemberdayaan Usaha Kecil Menengah di Dinas Koperasi dan UKM Provinsi Banten - Nurjanah, Siti; Achmad, Mansyur; Gatiningsih, Gatiningsih (JUDICIOUS, 2025)
The high percentage of poor people in Banten Province, the decreasing number of small and medium businesses in Banten Province during Covid 19, the decreasing income for small and medium businesses in Banten Province. The digital literacy of SMEs is still low due to technology. This research aims to analyze the implementation of small and medium enterprises (SMEs) empowerment policies at the Banten Province Cooperatives and SMEs Service. The method used in this research is descriptive qualitative using a two- dimensional analysis tool proposed by Marilee S. Grindle, namely Content of Policy and Context of Policy, data collection through interviews, observation and documentation. This research focuses on how the policy is implemented and the factors that influence its success. The research results show that the implementation of SMEs empowerment policies in Banten Province experiences various challenges, including limited resources, lack of coordination between institutions, and low community participation. However, there have been significant efforts by local governments to increase access to capital and training for SMEs. This research also identifies the importance of support from various parties, including the community and the private sector, in achieving the goal of economic empowerment. The conclusions of this research emphasize the need for a more integrated and collaborative strategy in implementing SME empowerment policies, as well as the need for regular evaluation to ensure the effectiveness of the programs being implemented. It is hoped that this research can contribute to the development of better policies in empowering SMEs in Indonesia.